Effects of temperature, shearing time and rate of shear on the viscosity of chitosan/agar-blend solutions - El-hefian, E.A.; Yahaya, A.H. (2010)
In this study, a number of aqueous solutions of chitosan/agar blends (with chitosan as the major component) were prepared. The effects of temperature, shear rate and shearing time on the rheological property, i.e. the apparent viscosity, were investigated for the blend solutions. Results show that a non-Newtonian behaviour was pronounced at temperatures from 20 degrees C to 50 degrees C for all solutions and that a decrease in viscosity with increasing temperature was also observed. It was also found that all the blend solutions obeyed the Arrhenius equation to different degrees. In addition, shearing time independence was found to occur at a low shear rate only for pure chitosan solution. However, the shearing time independence slowly shifted to occur at higher shear rate with increasing agar content.